OP0033 Systemic adenovirus mediated gene therapy using a chimeric soluble il-1 receptor type ii ?igg protein reduces acute inflammation in antigen-induced arthritis. (1st June 2001) - Dudler, J; Salvi, R; Busso, N; Chobaz-Péclat, V; So, A
Abstract : Background: The anti-inflammatory effects of IL-1 inhibition are well established but most studies have focused on the endogenous IL-1 receptor antagonist (IL-1Ra) protein. However, IL1ra has a very short plasma half-life and hundred-fold excess over IL-1 is required to obtain a 50% inhibition of IL-1 responses. Another naturally occurring inhibitor, soluble IL-1 receptor type II (sIL-1R2) may offer a higher IL-1 neutralising activity and several studies have emphasised its potential function as a regulatory "decoy" for IL1b. Objectives: To construct soluble IL-1 receptor type II chimeric protein with an IgG heavy chain and to evaluate its therapeutic potential in a murine arthritis model using a gene therapy approach. Methods: The murine IL-1R2 extracellular domain was cloned using a RT-PCR protocol from total cytoplasmic RNA, sequenced and a chimeric expressing gene constructed by the addition of a XbaI fragment encoding the constant and hinge regions of a murine IgG1 heavy chain. The IL-1R2IgG coding insert was subcloned into an E1-deleted adenoviral shuttle expression plasmid under the control of a CMV promoter and the resulting plasmid used to construct a standard first generation E1-deleted recombinant adenovirus (Ad-sIL1R2 Ig) using standard homologous recombination techniques in 293 cells. Stock viral preparations were produced in 293 cells and purified by ultracentrifugation in two CsCl 2 gradients. Viral titer (pfu/ml) was determined by plaque-assay. An EGFP (enhanced green fluorescent protein) expressing recombinant adenovirus (Ad-EGFP) was prepared using a similar protocol. Expression was confirmed by Western blotting using transient expression on HeLa cells under serum free-conditions. The therapeutic effects of this approach was tested in the acute murine antigen-induced arthritis model (AIA). Results: Western blotting under reducing and nonreducing conditions confirmed expression and dimerization of the chimeric protein. More importantly, adenovirus-mediated systemic expression of sIL1R2 Ig suppressed acute inflammation in vivo in murine AIA. Mice were injected into the tail vein with 109 pfu Ad-sIL1R2Ig or Ad-EGFP three days before induction of arthritis by intraarticular injection of 100μg mBSA into the right knee. The left knee was injected with PBS as a control. Joint inflammation determined by 99technetium pertechnetate uptake69 was statistically significantly decreased at day 3 and 7 post-injection in animal treated with Ad-sIL1R2 Ig as compared to Ad-EGFP (10 animals per group, 2 experiments) but proteoglycan depletion of cartilage did not appear to be diminished. Conclusion: Our study demonstrated the value of a soluble IL1R2Ig chimeric protein has a IL1 inhibitor in vivo . It also demonstrated adenovirus-mediated gene expression allow for sufficient level of expression. But our preliminary data also raise new questions of the respective values and roles of IL1 or TNFa inhibition regarding acute inflammation and cartilage degradation.